Status of Livestock Production in Gurez Valley of Jammu and Kashmir in India - KHAN, A. A.; DAR, A. A.; KHAN, H. M.; MIR, M. S.; MALIK, A. A.; AFZAL, Y. (Indian Journal of Hill Farming, 2014)
Livestock production situation in agro-pastoral production system of Gurez sub-valley of Kashmir was assessed based on field visits and interview of selected households as well as group discussion with community leaders. The survey showed that livestock was the main source of income; followed by agriculture and off-farm activities. Among the livestock, cattle were the most important livestock species followed by sheep, horse and chicken. The main feed resources of the area were highland pastures, forest lands, common property resources and cultivated fodders; the production of these are also decreasing due to lack of required scientific interventions. Productivity of animals in terms of milk production, growth rate and reproductive performance was generally low owing to primitive livestock breeding and rearing practices, scarcity of feed and fodder, migration of labour and lack of extension support services.